Mahligai Hotel / Ikhwan Mat Yasin @ Hashim ... [et al.] - Mat Yasin @ Hashim, Ikhwan; Abdullah, Mohd Firdaus; Mat Rani, Kamaruzzaman; Wan Ibrahim, Mohd Nizam; Mohd Nawi, Mohd Saiful Anan (2005)
Business plan is usually prepared before a business can be formed. It is important to have business plan because it determines the availability of the venture in a designed market. The business plan also gives principle plan, which gives a picture to the entrepreneur to take a step of action for starting a new business. So, it will be a guide line to manage our business efficiently. Mahligai hotel is established our result of our survey and research to provides 4 star hotels at Langkawi Island. We took this place as our main operation location because it has the strategically element as our needs to encourage our business promotion and services. As we already known, Langkawi Island is one of the most popular places to visit in Malaysia. We provide a rental service of guest room, ballroom, seminar and conferences room, health spa and others. Besides, we also develop our hotel with Bali and British concept. We make a different concept so that we can attract the tourist to stay at our hotel. Membership card will give to the people who would like to be our membership. They will get a lot of advantages when they stay at Mahligai hotel. But, the most important features of our business are to offered a good quality of services instead of reasonable price and fulfill customer satisfaction.